Perceptions and Experiences of Families of Infants Diagnosed with X-Linked Adrenoleukodystrophy (X-ALD) via Newborn Screening in Georgia and Kentucky - Sharanya Iyer; Aileen Kenneson; Nadia Ali; Gwen Gunn (Journal of Primary Care & Community Health)
Introduction: Newborn screening (NBS) for X-linked adrenoleukodystrophy (X-ALD) was added to the Recommended Uniform Screening Panel (RUSP) in 2016 to enable early diagnosis and treatment. This study aimed to understand the experiences of parents/caregivers of children with X-ALD to improve the NBS process and referral to appropriate clinicians. Methods: Parents/caregivers were recruited through NBS coordinators and genetic counselors in 6 states. Semi-structured interviews were conducted via Zoom. Two coders independently coded transcripts using MAXQDA software, and thematic analysis was conducted. Results: Four mothers and 3 fathers (for a total of 4 affected children) were interviewed. Before NBS, some parents were unaware of the purpose of the heel prick test. During the screening process, parents expressed mixed emotions of confusion, anxiety, and fear. Most lacked understanding of X-ALD and did not like the way the information was disclosed. All were referred to genetics and had positive feedback on this interaction. All were followed by endocrinology and neurology. Barriers included lack of access to clinics during the COVID-19 pandemic and lack of PCPs’ knowledge about X-ALD. Conclusion: Overall, parents were grateful for NBS but expressed concerns about the medicalization of their children’s childhood. The referral process is divided into 3 stages: screening, diagnostic, and treatment/management. Parents had both positive and negative feedback at various points in the referral process. Study results will help improve the NBS referral process in the Southern US and have implications for other locations that may choose to add X-ALD to their NBS programs in the future.